Probing amyloid beta dynamics in the brain using distinct strains of the neurotropic parasite Toxoplasma gondii: Molecular and cell biology/APP/Abeta/amyloid. (7th December 2020) - McGovern, Kathryn E.; Cabral, Carla M.; Koshy, Anita A.
Abstract: Background: Data suggest that amyloid beta (Aβ), produced by processing of the amyloid precursor protein, is a major initiator of Alzheimer's disease (AD) and a highly conserved anti‐microbial peptide. To gain new insights into Aβ modulation, we sought to harness the power of the coevolution between the neurotropic parasite Toxoplasma gondii and the mammalian brain. Prior studies attributed Toxoplasma ‐associated protection against Aβ to increases in anti‐inflammatory cytokines (TGF‐β and IL‐10) and infiltrating phagocytic monocytes. These studies only used one Toxoplasma strain making it difficult to determine if the noted changes were associated with Aβ protection or simply infection. Method: To address this limitation, we infected an AD mouse model with each of the genetically distinct, canonical strains of Toxoplasma (type I, type II, or type III) and assessed plaque burden, immune cell infiltration, and cytokine levels in the brain. We also assessed Aβ's role in coordinating the immune response against the parasite by acting as a chemokine for infiltrating immune cells. Additionally, Aβ's action against the parasite itself was assessed. Result: We found that only type II infection was protective against Aβ deposition. Both strains elicited increased numbers of CNS T cells and myeloid lineage cells as well as elevated pro‐inflammatory cytokines, but neither group showed a >2‐fold elevation of TGF‐β or IL‐10 at the protein level. In addition to providing protection, we have gone on to show that type II infection can reduce amyloid plaque burden in mice that already exhibited plaque deposition. We also determined that infiltrating macrophages in the type II inflammatory environment are most efficient at clearing Aβ. Conclusion: These data suggest that we can now use our identification of protective (type II) and nonprotective (type III) Toxoplasma strains to determine what parasite and host factors are linked to decreased Aβ burden rather than simply with infection. Current work is focused on defining the point at which amyloid clearance peaks, phenotyping the immune cell infiltrates that contribute to clearance, at which point excess Aβ is beneficial to the host, and whether the parasite may actively subvert the antimicrobial actions of Aβ.